Covalent and ionic Cu(II) complexes with cyclam and substituted benzoato ligands: structural, thermal, redox and mesomorphic properties - Abdullah, N.; Arifin, Z.; Tiekink, E.R.T.; Sharmin, N.; Ahmad Tajidi, N.S.; Mat Hussin, S.A. (Taylor & Francis, 2016)
A covalent mononuclear complex, [Cu(p-HOC6H4COO)2(cyclam)] (1), and two ionic mononuclear complexes, [Cu(cyclam)(H2O)2](p-CH3OC6H4COO)2 (2) and [Cu(cyclam)(H2O)2](p-CH3(CH2)15OC6H4COO)2·H2O (3), were formed from reaction of cyclam with [Cu2(p-HOC6H4COO)4(H2O)2], [Cu2(p-CH3OC6H4COO)4(H2O)2] and [Cu2(p-CH3(CH2)15OC6H4COO)4(H2O)2], respectively. These complexes were isolated as purple crystals with molecular structures showing distorted octahedral N4O2 geometry. Complexes 1 and 2 were irreversibly reduced to Cu(I) and oxidized to Cu(III), while 3 was redox inactive. Complex 2 reacted with N-(hexadecyl)isonicotinamide (L) to form [Cu(cyclam)(L)2](p-CH3OC6H4COO)2 (4). These complexes were thermally stable (Tdec > 200 °C for 1-3 and 174 °C for 4). Complexes 3 and 4 behaved as ionic liquids (melting temperatures lower than 100 °C) and exhibited mesomorphism.